Vocational teachers' autonomy in developing problem-based mathematics learning evaluation integrated with the design for change - Suryawan, I Putu Pasek; Pujawan, I Gusti Ngurah; Mahayukti, Gusti Ayu (Indonesian Journal of Educational Development (IJED), 2025)
Teachers’ experience and autonomy in designing evaluations often overlook the needs of students with special needs, a key component of inclusive education in vocational high schools. The integration of the Design for Change (DfC) approach, a component of design thinking, is regarded as a relevant approach to bridge mathematics learning with both inclusivity and industry relevance. This study explores the impact of integrating the DfC approach supported by teachers’ understanding of evaluation on the autonomy of inclusive vocational school teachers in developing problem-based mathematics learning evaluations. Using a mixed-methods approach with an explanatory sequential design, data collection began with a quantitative phase involving 114 mathematics teachers from inclusive SMK Pusat Keunggulan in Bali, selected through cluster random sampling. Data were analyzed using multiple linear regression and t-tests. The qualitative phase involved two purposively selected teacher informants, with data gathered via semi-structured interviews and analyzed descriptively. Findings reveal that teachers with a strong understanding of the DfC tend to show greater autonomy in designing problem-based mathematics learning evaluations aligned with both student needs and vocational demands. The DfC approach is shown to support mathematics teachers in creating innovative, inclusive, and industry-relevant evaluations.